Benign cystic mesothelioma of omentum: Mimicking abdominal lymphangioma - Bhargavi, Mallidi; Bollimuntha, Sujana; Boyidi, Venkata Raju; Nayak, Samir Ranjan (Indian Journal of Case Reports, 2020)
Benign multicystic peritoneal mesothelioma (BMPM) or benign cystic mesothelioma is a very rare disease characterized by proliferative lesions of the peritoneal mesothelial cells mainly in the pelvic or abdominal cavity. It occurs predominantly in young to middle-aged women and the majority of cases were associated with a history of abdominal or pelvic operation, a history of endometriosis, and pelvic inflammatory disease. BMPM involving only the omentum is not mentioned in the literature; here, we present a unique case of BMPM which was diagnosed as cystic lymphangioma with differential diagnosis of pseudomyxoma peritonei in a 40-year-old patient presenting as recurrent abdominal pain.